2019
DOI: 10.1111/jace.16329
|View full text |Cite
|
Sign up to set email alerts
|

Defect dipole evolution and its impact on the ferroelectric properties of Fe‐doped KTN single crystals

Abstract: The ferroelectric and piezoelectric properties of doped potassium tantalum niobate crystals with different Fe doping amounts and the adjustability of the properties are investigated. The hysteresis loops and current density curves show that the defect dipoles have an obvious effect on domain reorientation, and the effect decreases with increasing doping amount. The ferroelectric and piezoelectric properties can be adjusted via the defect dipoles, and the adjustability is reduced with increasing doping amount. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The results of XRD are shown in Figure d. According to the diffraction angles (2θ) of anisotropic planes, the lattice constant a is calculated (∼3.99 Å), which is consistent with previous reports . This suggests that the impact of inaccurate cutting on the performance of the anisotropic EC properties is avoided.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of XRD are shown in Figure d. According to the diffraction angles (2θ) of anisotropic planes, the lattice constant a is calculated (∼3.99 Å), which is consistent with previous reports . This suggests that the impact of inaccurate cutting on the performance of the anisotropic EC properties is avoided.…”
Section: Resultssupporting
confidence: 88%
“…According to the diffraction angles (2θ) of anisotropic planes, the lattice constant a is calculated (∼3.99 Å), which is consistent with previous reports. 23 This suggests that the impact of inaccurate cutting on the performance of the anisotropic EC properties is avoided. The temperature dependence of relative permittivity (ε r ) and dielectric losses (tan δ) of the three samples is shown in Figure 1e.…”
Section: Resultsmentioning
confidence: 99%
“…24) The ferroelectric to paraelectric phase transition temperature, and hence the dielectric, ferroelectric and EO properties can be modulated by tuning the composition ratio of Ta/Nb. 23,25,26) However, the growth of high quality KTN films required for the state of the art thin-film-based plasmonic EO devices remains challenging. Our previous work confirmed that epitaxial (001) KTN films with near stoichiometric composition possess a linear EO response and large EO coefficient of 49 pm V −1 among the reported values.…”
Section: Introductionmentioning
confidence: 99%
“…However, highly doped Fe ions can reduce the dielectric permitivity because of the excessive “locked” size and direction of polarized regions . In addition, doping Fe also affects the polarization–electric field loops through controlling the concentration of Fe ions . Mn doping can enhance the piezoelectric properties of KTN owing to the enhanced IMI, resulting in weaker dipole correlation and increased local polarization .…”
Section: Introductionmentioning
confidence: 99%